Protease and chitinase activity of Trichoderma isolates and their synergy with biochar in enhancing chickpea defense related enzymes - Kumari, Ranjna; Koul, Bhupendra; Kumar, Vipul; Kumar, Adesh; Somal, Manpreet Kaur; Sachan, Rohan Samir Kumar (Frontiers in Microbiology, 2025)
BackgroundSoil-borne pathogens such as Sclerotium rolfsii (Agroathelia rolfsii Sacc.) and Fusarium oxysporum f. sp. ciceri pose serious threats to chickpea (Cicer arietinum L.) production. Trichoderma spp. are widely recognized in modern agriculture as effective biocontrol agents due to their ability to produce several lytic enzymes, including chitinases, glucanases and proteases, which contribute to the inhibition of plant pathogens.ObjectivesThis study aimed to screen Trichoderma isolates for protease and chitinase activity, evaluate their antagonistic potential against two chickpea pathogens, and assess the synergistic effects of Trichoderma and biochar in disease suppression and plant growth promotion. This study investigated the protease and chitinase activities of different Trichoderma isolates and evaluated their synergistic potential with biochar in promoting defense-related enzymes in chickpea (Cicer arietinum L.).MethodsA total of 21 Trichoderma isolates were screened for protease and chitinase activity. Four potent strains—T. harzianum (PBT13), T. virens (PBT3), T. lixii (PBT14), and T. asperellum (PBT4)—were selected for further evaluation. Antagonistic activity against F. oxysporum f. sp. ciceri and S. rolfsii was assessed using dual culture assays and scanning electron microscopy (SEM). The extracellular chitinase activity of the most active strain was quantified, and its inhibitory effect on pathogenic growth was determined. The combined application of T. harzianum and rice husk biochar significantly influenced disease incidence, defense enzyme activity, germination, chlorophyll content, sclerotia formation, and Trichoderma survivability under greenhouse and field conditions.ResultsAmong the tested isolates, T. harzianum (PBT13) showed the highest enzymatic activity and strong antagonism against both pathogens. Extracellular chitinase activity peaked at 60 U/mL, suppressing in vitro growth of F. oxysporum f. sp. ciceri by 95.95% and S. rolfsii by 97.10%. Greenhouse/field trials revealed that combining T. harzianum with rice husk biochar significantly reduced disease incidence, enhanced plant defense, enzyme activity, improved germination and chlorophyll content, reduced sclerotia formation, and promoted Trichoderma survival in soil.ConclusionThe study demonstrates that enzyme-active Trichoderma strains, particularly T. harzianum (PBT13), in combination with rice husk biochar, provides a sustainable and synergistic approach for managing soil-borne diseases in chickpea. This integrated strategy not only suppresses pathogens but also improves plant health and resilience, offering a viable alternative to chemical fungicides.